THE STUDY OF COPPER EXTRACTION FROM DETOXIFICATION OF GOLD ORE PROCESSING TAILINGS WITH GRAPHITE AND FLUX AT 1100 â 1300 Â°C - Lanjar Grahita Mahardika, R
Gold ore processing by heap leach method uses cyanide solution to leach the gold from within the ore. The leaching with cyanide solution also leads to the dissolution of copper from the ore. The copper in the solution is not recovered during the adsorption process and is accumulated in the solution reducing the effectivity of gold and silver adsorption. Therefore, the copper-rich leach solution can not be used further and must be processed through detoxification process so that the disposed water meets the standard quality requirements. The detoxification process produces tailing in the form of sludge with high copper content (46%). The objective of this research is to extract copper at high temperatures from the detoxification tailing. Moreover, analysis of processing route and raw material cost are also performed using METSIM software. The experiment started with the preparation and characterization of the detoxification process tailings using X-ray Powder Diffraction (XRD), X-ray Fluorescence (XRF), Inductively Coupled Plasma (ICP) dan Scanning Electron Microscope – Energy Dispersive Spectroscopy (SEM-EDS). After the composition of detoxification tailing had been identified, the flux composition and the addition of graphite reducing agent were determined. The flux types implemented in this study are SiO2 + H3BO3 and SiO2 + Al2O3 so as to form slag which can be separated from the molten metal. The reductions were carried out by using the isothermal method with temperatures of 1100, 1150, 1200, 1250 and 1300 °C for 2 hours in the muffle furnace. The product metal was weighted to calculate the metal recovery and was examined using SEM-EDS to measure composition and distribution of elements in the metal. By using METSIM, optimum parameters and condition from the experiments were then used to evaluate the performance of different smelting technologies, i.e. reverberatory furnace and electric furnace. The CaO-SiO2-B2O3 slag system showed stable metal recovery in the range of 90% at each temperature, with the highest metal recovery of 91.25%. Whereas in the CaO-SiO2-Al2O3 slag system, the increase of metal recovery was proportional to the increase of temperature reaching 100%. The CaO-SiO2-Al2O3 slag system with temperature of 1250 °C was selected as the basis for the METSIM simulation. The simulation result showed that the reverberatory furnace had higher operating costs (Rp1.083.732,71) than that of the electric furnace (Rp640.382,31) at the same parameters and condition.